Electron Doping Effect in the Resistive Switching Properties of Al/Gd 1- x Ca x MnO 3/Au Memristor Devices - Lähteenlahti Ville; Schulman Alejandro; Beiranvand Azar; Huhtinen Hannu; Paturi Petriina (American Chemical Society, 2022)
We report on the resistive switching (RS) properties of Al/Gd1–xCaxMnO3 (GCMO)/Au thin-film memristors. The devices were studied over the whole calcium substitution range x as a function of electrical field and temperature. The RS properties were found to be highly dependent on the Ca substitution. The optimal concentration was determined to be near x = 0.9, which is higher than the values reported for other similar manganite-based devices. We utilize an equivalent circuit model which accounts for the obtained results and allows us to determine that the electrical conduction properties of the devices are dominated by the Poole–Frenkel conduction mechanism for all compositions. The model also shows that lower trap energy values are associated with better RS properties. Our results indicate that the main RS properties of Al/GCMO/Au devices are comparable to those of other similar manganite-based materials, but there are marked differences in the switching behavior, which encourage further exploration of mixed-valence perovskite manganites for RS applications.